Unlocking the Potential of Women Entrepreneurs in Uganda : A Brief of Policy Interventions - Copley, Amy; Gokalp, Birce; Kirkwood, Daniel (World Bank, Washington, DC, 2021)
Private sector development is an integral channel through which countries can better leverage the productive potential of the youth bulge, support job creation, and maintain social stability. Entrepreneurship already plays an important role in Sub-Saharan Africa, where forty-two percent of the nonagricultural labor force is self-employed or is an employer, the highest rate in the world. Women business owners in Uganda face several gender-specific barriers to their enterprise performance, including lower levels of innovation, lower use of capital and labor, and segregation into lower-value sectors. This brief focuses on the policy interventions that can help empower women entrepreneurs across Uganda.